The Impact of Hippocampal Sex Hormones Receptors in Modulation of Depressive-Like Behavior Following Chronic Anabolic Androgenic Steroids and Exercise Protocols in Rats - Selakovic, Dragica; Joksimovic, Jovana; Jovicic, Nemanja; Mitrovic, Slobodanka; Mihailovic, Vladimir; Katanic, Jelena; Milovanovic, Dragan; Pantovic, Suzana; Mijailovic, Natasa; Rosic, Gvozden (Frontiers in Behavioral Neuroscience, 2019)
The aim of this study was to evaluate alterations in depressive-like behaviors in rats following chronic administration of a supraphysiological dose of anabolic androgenic steroids (AASs) as well as exposure to a prolonged exercise protocol. The role of hippocampal sex hormones receptors in the modulation of depressive-like behavior was also assessed. A total of 48 male Wistar albino rats were divided into six groups: control, exercise (1 h/d, 5 consecutive days), nandrolone-decanoate (ND, 20 mg/kg/w, in a single dose), exercise plus nandrolone-decanoate, testosterone-enanthate (TE, 20 mg/kg/w, in a single dose), and exercise plus testosterone-enanthate. After the six-week protocols were complete, the rats underwent behavioral testing in the tail suspension test (TST). Rats were sacrificed for the collection of blood samples, to determine sex hormones levels, and isolation of the hippocampus, to determine (androgen receptors – AR and estrogen receptors α – ERα expression. ND and TE treatment induced significant depressive-like behavior, opposing the antidepressant effect of exercise . Chronic TE administration elevated testosterone (T) and dihydrotestosterone (DHT) serum levels, and this was augmented by exercise. In contrast, ND and exercise alone did not alter T or DHT levels. There were no changes in serum estradiol levels in any of the groups. Immunohistochemical analysis showed that exercise reduced AR immunoreactivity in all hippocampal regions and increased the ERα expression in the CA1, dentate gyrus, and total hippocampal sections, but not in the CA2/3 region. AASs administration increased AR expression in all hippocampal regions, although not the total hippocampal section in the TE group and did not significantly decrease ERα. The hippocampal AR/ERα expression index was lowered while parvalbumin- immunoreactivity (PV)was enhanced by exercise. AASs administration increased the AR/ERα index and reduced PV-immunoreactivity in the hippocampus. The number of PV-immunoreactive neurons negatively correlated with the antidepressant effects and the AR/ERα ratio. Our results suggest a potential role of the numerical relationship between two sex hormones receptors (stronger correlation than for each individual receptor) in the regulation of depressive-like behavior via the hippocampal GABAergic system in rats, which allow better understanding of the hippocampal sex hormones receptors role in modulation of depressive-like behavior.